Enhancing the entrepreneurial skills of rural farmers through digital technology and business innovation - Brillyanes Sanawiri; Moh. Fahrial Amrulla (University of Merdeka Malang, 2025)
This community service program aimed to empower farmers in the Taman Madani Farmers' Community, Nongkojajar, by enhancing entrepreneurial skills through digital technology and business innovation. Over 14 weeks, the Agriculture Community Business Creation Program provided training and mentorship to 40 participants on micro-enterprise development, covering business planning, financial management, digital marketing, and product innovation. The program was conducted in four phases: preparation, training, independent business initiation, and development. Participants were introduced to digital tools like Facebook for marketing, along with practical business planning exercises. Despite challenges such as limited internet access, the program significantly improved participants' understanding of business management, marketing, and product development. Many began adopting digital platforms to expand their market reach, increase sales, and improve product competitiveness. The results demonstrated substantial progress in business operations, with participants showing greater confidence in managing their enterprises. Moving forward, recommendations include expanding access to financial support, increasing the frequency of training sessions, and providing continuous mentorship to ensure sustainable business growth and long-term success. By fostering innovation and digital adoption, this program has helped rural farmers build more resilient and competitive businesses in an increasingly digital economy.